PENGARUH PUPUK BOKASHI KOTORAN SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH PADA ULTISOL PUOSU JAYA KECAMATAN KONDA, KONAWE SELATAN - TUFAILA, MUH; YUSRINA, YUSRINA; ALAM, SYAMSU (Jurnal Agroteknos, 2014)
This study aimed to determine the effect of the use of bokashi fertilizer on Rice productivity in Ultisol Puosu Jaya, Konda district, South Konawe, conducted on April to September 2013.  The study was arranged in randomized block design (RBD) with a single factor pattern, consisted of eight bokashi fertilizer treatments with three replications, namely: without bokashi fertilizer (K0), dose of  5 tons ha-1 (K1), dose of 7.5 tons ha-1 (K2), dose of 10 tons ha-1 (K3), dose of 12.5 tons ha-1 (K4), dose of 15 tons ha-1 (K5), dose of 17.5 tons ha-1 (K6) and dose of 20 tons ha-1 (K7), so that there were twenty four experimental units.  Observed variables included the growth and production of plants, soil analysis before and after treatment as well as the analysis of the quality of the fertilizer used.  Data were analyzed using analysis of variance followed by Duncan’s Multiple Range Test. The result showed that the use of compost at Ultisol dose of 12.5 tons ha-1 (K4) gave the best effect on the growth and production of rice in Ultisol Puosu Jaya, Konda district, South Konawe. However, the effect of this treatment did not significantly different with the effect of dossages of 5 and 7.5 tons ha-1 with reached resultof 7.6 and 8.4 tons ha-1, respectively.Keywords : bokashi, rice, Ultisol.